The Philippine Military Academy Library a survey - Estavillo, Corazon C. (1978)
This study is a survey of the existing conditions of the Philippine Military Academy Library as of late 1977. It reports on the status of the library's collection, financial resources, staff resources, technical services, reader's services, and physical plant.